Effect of water table depth and tillage methods on plant-water status and yield of rice - Maurya, P.R.; Lal, R. (1981)
Effects of water table depths on plant-water status, and on growth and yields of two rice varieties (TOS 78 and TOS 848) were studied in a lysimetric investigation. A field study was also conducted on a hydromorphic soil to investigate the effects of fluctuating water table on rice. The leaf-water potential of TOS 78 monitored at 1300 hours at 50% flowering stage was −17.5 and −23.0 bars for 0 and 60 cm water table depths, respectively. When grown under soil moisture stress, TOS 848 maintained higher leaf-water potential (−17.5 barvs −22.5 bar) and yielded more than TOS 78. Under hydromorphic soil conditions, no-tillage treatments yielded the same as conventionally tilled plots.